The architecture of Chinese-English microcomputer systems - Huang, J.; Liu, T.; Archer, Norman P.; Chan, M.W. Luke; McMaster University, Faculty of Business (My University, 1986)
Computing in the People' s Republic of China has recently begun to gain momentum and, because of China's large population, its computing requirements are of world wide interest. Much of the recent advances in computing in the People's Republic of Chin a (PRC) have occurred in the are a of microcomputer software. In particular, systems have been developed which allow the use at· will of both Chinese and English as needed. This greatly improves the ease of using already developed English application soft are, but with a Chinese language interface. The greatest difficulty in developing Chinese language software has been in the entry of Chinese characters, but a number of efficient methods have been developed to handle this problem. Methods of displaying , printing, and communicating Chinese characters, as well as mixing Chinese with English on micocomputer systems, have all been developed and are constantly being improved.
22, 2 leaves : ; Includes bibliographical references (leaves 20-22). ; "December 1986."
Keywords: Business; Business; Microcomputers > China Chinese character sets (Data processing) Chinese language > Translating into English > Computer programs English language > Translating into Chinese > Computer programs